2019
DOI: 10.1155/2019/4376851
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Computer Tomography Assisted Radiofrequency Ablation in the Treatment of Osteoid Osteoma

Abstract: Background. Osteoid osteoma (OO) is one of the most commonly occurring benign bone tumors. It constitutes 10-12% of benign bone tumors and 2-3% of primary bone tumors. In radiofrequency ablation (RFA) treatment, the cells of the tumor are thermally inactivated by the help of electrodes shaped like needles. In our study, we aimed to show the major and minor complications in patients undergoing RFA and to show what should be done to prevent these complications. Methods. The study was carried out as a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The proximal femoral constitutes the most susceptible part for OO, which is challenging to treat because of its deep location, close to the hip joint, and complex local anatomy [4,14,15,17,24]. Presently, the main surgical treatment methods for OO include open surgical resection and minimally invasive treatment, such as CT guided radiofrequency ablation (RFA) [25][26][27][28], cryoablation [17], and microwave ablation [29]. Whatever the kind of treatment adopted, the key to successful surgical treatment of OO is based on the accurate location of the nidus and its subsequent complete removal [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proximal femoral constitutes the most susceptible part for OO, which is challenging to treat because of its deep location, close to the hip joint, and complex local anatomy [4,14,15,17,24]. Presently, the main surgical treatment methods for OO include open surgical resection and minimally invasive treatment, such as CT guided radiofrequency ablation (RFA) [25][26][27][28], cryoablation [17], and microwave ablation [29]. Whatever the kind of treatment adopted, the key to successful surgical treatment of OO is based on the accurate location of the nidus and its subsequent complete removal [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…However, it requires high hardware conditions, high technical operation requirements, presents with incomplete removal of the nidus, easy to damage adjacent tissues, and unable to carry out a pathological examination, and among other limitations, which affect its popularization and application [8,17,25,[30][31][32]. At the same time, minimally invasive surgery is signi cantly inferior to open surgical resection in terms of OO recurrence rate and incidence of complications [25,29,33,34]. The trauma associated with open surgery is relatively higher but wholly and accurately results in the removal of the nidus, improving the positive rate of pathological examination, and reduces the postoperative recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on atypical localizations, Akhlaghpour et al[ 6 ] reported skin burns in a patient with phalanx localization. Oç et al[ 25 ] reported that two of 87 patients exhibited second-degree skin burns in the anterior part of the tibia and one patient with metacarpal localization experienced numbness. Based on these data, traditional open surgery may be recommended as the primary treatment, particularly in localizations having insufficient soft tissue support, localizations close to neurovascular structures, and some atypical localizations.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate is low (range: 1-6%). 30 The most common complication is a skin burn in the treated site, followed by local infection, necrosis of the adjacent structures, and postintervention fractures. Minor complications are loss of sensitivity in the treated site that generally improves spontaneously in 2 weeks.…”
mentioning
confidence: 99%